Physicochemical Properties and Microstructure of Mixed-species Surimi Made from Decapterus sp. and Priacanthus sp. - Sihono, Sihono; Purnomo, Agus Heri; Wibowo, Singgih; Subaryono, Subaryono; Suryaningrum, Theresia Dwi; Utomo, Bagus Sediadi Bandol; Dewi, Fera Roswita (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2024)
The surimi industry plays a substantial role in bolstering Indonesia’s fishing sector. The collapse of the majority of surimi companies can be attributed to the                   government limitation on trawling, which served as the primary source of demersal fish utilized in surimi processing. This restriction resulted in a significant shortage of raw material for industry. Therefore, it is imperative to explore alternate fish species that can serve as viable raw materials for the production of surimi.  Alternative fish species are needed as raw materials for surimi. The objective of this work was to investigate the physicochemical characteristics and microstructure of surimi produced from two distinct Indonesian fish species: Decapterus sp., a pelagic species, and Priacanthus sp., a demersal species. Five ratios of Decapterus sp and Priacanthus sp; 1:0 (F1: control 1),  3:1 (F2), 1:1 (F3), 1:3 (F4), and 0:1 (F5: control 2) were tested. The proximate composition showed that the addition of Decapterus sp. to the formula increased the protein and fat content of mixed surimi. The formula F4 showed the highest value for almost all textural profile parameters; there were springiness, cohesiveness, gumminess, chewiness, and resilience. The same result also presented in the gel strength, F4 also has the highest value. The Water Holding Capacity value was low, and it showed no difference between all formulas. The whiteness value was in the range of 66-68, and it showed no difference between all formulas. Protein patterns showed no myosin heavy chain in all formulas. Microstructure analysis showed that only F5 (control 2) was compact and denser, but the other formulas (F1, F2, F3, and F4) showed a large number of loose and porous structures. In the microbial analysis, all formulas showed the Total Plate Count value ( 6 x 105 cfu/g) was under the maximum acceptable value (107 cfu/g). The findings of the study indicated that the mixed-surimi, consisting of Decapterus sp and Priacanthus sp at a ratio of 1:3, exhibited the highest level of gel strength. In conclusion, Decapterus sp has the potential to serve as a viable raw material when combined with Priacanthus sp.